An Analysis of Bank’s Loan Loss Provision Behaviour: A Comparative Study of Thailand and the Philippines - Yang, Chu Yu (2013)
The recent proposal of the ASEAN banking integration framework that aims to harmonized the regulation and reporting standard of all ASEAN member states stimulated debate on the feasibility of its implementation and whether its inception would enhance the wellbeing of the ASEAN economy. This study contributes to the ongoing debate by assessing the compatibility of banking system in Thailand and Philippines regarding banks’ provisioning decision with sample data consisted of 55 banks spanning from 2006 to 2012. The GMM estimation result demonstrates that many banks manipulate their income by adjusting the level of non-performing loan to fulfill regulatory capital requirement which explains the absence of capital management through loan loss reserve. The study finds inconclusive result for the synchronization of business cycle and lending cycle; therefore, whether Thai and Philippine banks’ provisioning policy exhibit pro-cyclicality is uncertain. Findings in this study suggest that the banking systems in both countries are rather harmonized and with the adoption of Basel III, the implementation process of the ABIF should be rather smooth.